Academic Information System Success Model and Maturity Level Comparison for Improvement Recommendation - Sukarno Bahat Nauli; Pualam Dipa Nusantara; Agung Priambodo (Fakultas Ilmu Komputer, 2022)
Evaluation of a system is needed to determine whether the system is still in accordance with organizational goals. Academic information system is a system that aims to perform data processing so that it can provide convenience for users in academic administrative activities. This study purposes to determine the level of governance maturity in the Monitor and Evaluate domain of academic information systems at Satya Negara Indonesia University and determined factors of the success of the information system. The results of the measurement process shown that the maturity level of the system is at level 2.1 and the factors that affected the success of the system are System Quality, Quality of Service, User Satisfaction and Net Benefits. The comparison specifically on System Quality and User Satisfaction relation has less significant impact (0.2) while IT Performance of Monitor and Evaluate process is at initial/ad hoc stage (level 1). In this study the Quality of Information has no affect on the success of the system. The results of this study provide recommendations for organizations to improve governance according to organizational goals to level 3 and to improve the Quality of Information of information systems.